Pengaruh Penambahan Bakteri Pseudomonas Sp. Terhadap Degradasi Pestisida Berbahan Aktif Profenofos Pada Media Tanah - Nora Aprilin; Aryo Sasmita; Elvi Yenie (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The needs for agricultural products are increasing along with population growth, but the area of agricultural land is decreasing and so as plant pest organisms. Therefore, one of the intensifications of agricultural policies is to use pesticides. The aim of this study was to determine the efficiency of degradation of pesticide-contaminated soil with active ingredients profenofos in the bioremediation process with the addition of Pseudomonas sp. This study used a bioremediation reactor with a size of 20 cm x 35 cm, pesticides with active ingredients profenofos and pesticide residue testing carried out using Gas Chromatography-Mass Spectrometry (GC-MS) instrumentation. The research variables include variations in the concentration of the bacterium Pseudomonas sp. that is 2 ml/kg, 3 ml/kg and the control reactor with bioremediation time for 21 days. The results showed that the bioremediation method using Pseudomonas sp. able to set aside pesticide residues made from with active ingredients profenofos in soil media. Pollution removal efficiency for bacterial variation of 2 ml/kg was obtained of 93.67%, the bacterial variation of 3 ml/kg of 96.33% and control reactor was 76.33% with a residence time of 21 days.Keywords: Bioremediation, Profenofos, Pesticide Residue, Pseudomonas sp.